Mathematics in police activity: basics, features, mathematical training - S. O. Serbenyuk (Bulletin of Kharkiv National University of Internal Affairs)
The main attention is paid to the introduction of a comprehensive academic discipline “Mathematical Methods in Police Activity” for the first time and the discussion of the content of its first module for students of higher education institutions subordinated to the Ministry of Internal Affairs of Ukraine with the aim of combining mathematical methods, as well as elements of physics, astronomy and geography, in particular topography, to solve practical problems in the professional activity of police officers. Some components of the first module of this discipline are formulated on the basis of a study of an online course on mathematics for firefighters and rescuers in the United States.